The Efficacy of Nutrition Education on Anemia and Upper Arm Circumference among Pregnant Women in Aceh Besar District of Indonesia during the Covid-19 Pandemic - Ahmad, Aripin; Wagustina, Silvia; Dwiriani, Cesilia Meti; Estuti, Wiwit; Salfiyadi, Teuku; Arnisam, Arnisam; Fitrianingsih, Eva (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2022)
This study aimed to analyze the effects of nutrition education on anemia and upper arm circumference in pregnant women. It was a cluster-randomized control study involving 110 pregnant women. The nutrition education interventions, was a combination of offline and online sessions, conducted by trained Nutrition education staffs with a 1:5 ratio to pregnant women. Twelve education sessions were conducted for three months utilizing a nutrition booklet for pregnant women, food monitoring cards, and flyers shared on a social media WhatsApp group. The socio-demographic data were obtained through an interview method. The nutritional status collected, by measuring Mid Upper Arm Circumference (MUAC), and anemia was determined through a diagnosis by the family doctor. Data were analyzed using the chi-square test and the paired and independent t-tests, the confidence interval was set at 95%. Hemoglobin levels in the intervention group experienced a higher increase than in the control group. The MUAC in the intervention group increased by 0.8 cm while in the control group it was decreased by -2.7 cm. However, the Difference in Difference (DID) analysis did not show significant different for both parameters (p=0.198 and p=0.274). Chi square analysis showed that the prevalence of anemia at the end line point in the intervention group (3.6%) was significantly lower compared to the control group (14.5%) (p=0.047). The prevalence of the Chronic Energy Deficiency (CED) measured by MUAC decreased by 9% in the intervention group, and 1.8% in the control group. However, the difference in prevalence of CED was not statistically significant (p=0.696). The nutrition education within three months did not significantly increase the mean hemoglobin and MUAC. But considering the trend in decreasing anemia and CED prevalence in the intervention group, structured and routine nutrition education can be implemented as part of nutritional intervention in pregnant women to prevent anemia and CED to observe effects in a longer-term intervention.